Prevalence of hearing loss among primary school children in Mbarara, Uganda - Basan˜ez, Irving; Nakku, Doreen; Stangl, Susan; Wanna, George B. (International journal of pediatric otorhinolaryngology, 2015)
Introduction: Hearing loss in children is a common entity worldwide. We examined the prevalence and etiology of hearing loss among primary school children in Mbarara, Uganda. Methods: Cross-sectional study in primary school children aged 5–14 was performed to determine the prevalence of hearing loss. Ugandan primary school children were screened for disabling hearing loss (threshold >30 dB) and confirmatory audiometry was performed on those who failed the screening. Results: There were 639 children screened. Thirty-five (5.5%) of children screened failed and were referred for further testing. Two children were lost to follow-up. The percentage of children with true hearing loss was 3.1%. Conclusions: The incidence of failed hearing screening and hearing loss in Mbarara, Uganda is similar to other populations. Hearing loss is a significant problem in Uganda and efforts should be made for primary, secondary, and tertiary prevention of hearing loss.
Keywords: Africa; Hearing loss; Schoolchildren; Uganda; Hearing screening; Audiology